Curriculum Evaluation Models: Theoretical Analysis and Implementation in Modern Education Systems - Ahmad Fauzan Aminulloh; Nur Masyita Ramdhani; Moh Rifqi; Mohammad Yahya (Universitas Ibn Khaldun, 2026)
Curriculum evaluation is a systematic process used to assess the effectiveness, relevance, and achievement of educational objectives through analysis of all components of the curriculum, from planning and implementation to learning outcomes. This article comprehensively discusses various curriculum evaluation models used in modern education systems, including research models, goal-oriented models, goal-free models, multivariate mixed models, EPIC models, and CIPP models. Each model is analyzed based on its characteristics, approach, and contribution in providing a comprehensive overview of curriculum quality. Evaluation not only serves as a tool to determine the success rate of a program, but also as a basis for accountability, continuous improvement, and strategic decision-making in curriculum development. In addition to describing various evaluation models, this article also highlights the importance of the competence of evaluators, both internal and external, who have theoretical understanding, accuracy, objectivity, and professional skills in conducting evaluations. The results of the study show that the use of an appropriate evaluation model greatly influences the accuracy of the findings and recommendations produced, thereby improving the quality of learning and ensuring that the curriculum remains adaptive to developments in science and the needs of students. Thus, curriculum evaluation is an important instrument in maintaining the quality of education and supporting the effective and sustainable achievement of national education goals.